MEMAHAMI SECARA KRITIS PEMIDANAAN DALAM UNDANG-UNDANG PERBANKAN - Faisal Faisal (Fakultas Hukum Universitas Bangka Belitung, 2018)
General Purpose of punishment in criminal law at least can be divided into two : first ,this goal patterned conceptual gave basis of criminal sanctions, the type and form of criminal sanction. Second, the purpose of criminal sanctions against those who violate the criminal law. In the banking law, not explicitly mentioned purpose of criminal sanctions in specific meaning. But can be seen in the banking law has only a more general purpose .